General Economics and Teaching: What Is Wrong with Islamic Economics? Analysing the Present State and Future Agenda - El-Gamal, Mahmoud (Journal of Economic Literature, 2013)
Mahmoud El-Gamal of Rice University reviews, “What Is Wrong with Islamic Economics? Analysing the Present State and Future Agenda” by Muhammad Akram Khan. The Econlit abstract of this book begins: “Explores the state of the art in Islamic economics and finance, analyzes reasons for perceived stagnation, and considers a way forward. Discusses Islamic economics—state of the art; the “why” of Islamic economics; what is Islamic economics?; methodology of Islamic economics; the move from Islamic theology to Islamic economics; expanding the frontiers of economics; an Islamic economic system or spiritual capitalism?; elimination of interest—from divine prohibition to human interpretation; prohibition of riba in the primary sources of Islam; the theory of riba—the orthodox interpretation; assessment of the orthodox interpretation; modernist thinking on riba; prohibition of riba—the continuing debate; unresolved issues in the orthodox interpretation of riba; practice of interest-based finance among Muslims; prohibition of riba—the way forward; the theoretical basis of Islamic banking; problems of profit–loss sharing; practice of Islamic banking and finance; a trajectory of legal tricks—hiyal; Islamic insurance takaful; and contemporary application of the law of zakah. Khan is former Deputy Auditor General of Pakistan and Chief Resident Auditor of United Nations Peacekeeping Missions.”